Organic-inorganic hybrid electrochromic materials, polysilsesquioxanes containing triarylamine, changing color from colorless to blue. Issue 1 (December 2017) - Wang, Shuzhong; Cai, Shuwei; Cai, Wanan; Niu, Haijun; Wang, Cheng; Bai, Xuduo; Wang, Wen; Hou, Yanjun
Abstract Four kinds of soluble monomers, containing triarylamine (TAA) group with reactive siloxane group, were synthesized under mild conditions via the reaction between 3-(triethoxysilyl)propyl isocyanate (TEOSPIC) and four TAA derivatives, respectively. Then the corresponding colorless organic-inorganic hybrid materials (PSSOs) were derived from the hydrolytic condensation of the monomers. PSSOs revealed good solubility in polar solvents on account of the effect of propeller-like TAA unit as well as the auxo-action effect of the flexible chain within the monomers. The structural characteristics of these PSSOs were identified by1 H NMR, 29 Si NMR, FT-IR spectroscopies and X-ray diffraction (XRD). The morphology, dynamic changes of the transmittance and current before and after electro-oxidizing reaction were studied, and didn't show significant change suggesting good stability of the PSSOs. Meanwhile, these PSSOs performed high contrast of optical transmittance change up to 84% with the highest coloration efficiency to 241 cm2 ·C−1 . Furthermore, electrofluorescent properties of PSSOs were investigated with high-contrast.